2020
DOI: 10.1111/trf.15661
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal blood transfusion in South Africa: indications and practice in a high‐HIV‐prevalence setting

Abstract: BACKGROUND Globally, data on antenatal blood transfusion practices are scarce. We sought to characterize the epidemiology of antenatal transfusion in South Africa. STUDY DESIGN AND METHODS A cross‐sectional study was conducted of women who were transfused during pregnancy (>48 hr before anticipated delivery) at two hospitals in Durban and Soweto in 2014 to 2015. Medical record data on demographics, obstetric history, anemia, HIV status, and indications for blood transfusion were abstracted. RESULTS The records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Risk factors for anaemia other than iron deficiency should be considered, including the social determinants of health which predispose to common infections such as HIV and AIDS, TB and parasitic infestations, as well as obesity [ 3 ]. In the studies conducted in HIV positive cohorts, a positive association between anaemia and the condition was seen [ 5 , 18 20 , 31 , 18 , 34 , 35 , 37 , 41 , 44 , 47 , 51 ]. Globally, there is an increase in the prevalence of anaemia in HIV-positive patients and those with AIDS, possibly due to increased blood loss from concomitant neoplasia or gastrointestinal lesions, or due to decreased red blood cell (RBC) production, RBC destruction or inefficient RBC production.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for anaemia other than iron deficiency should be considered, including the social determinants of health which predispose to common infections such as HIV and AIDS, TB and parasitic infestations, as well as obesity [ 3 ]. In the studies conducted in HIV positive cohorts, a positive association between anaemia and the condition was seen [ 5 , 18 20 , 31 , 18 , 34 , 35 , 37 , 41 , 44 , 47 , 51 ]. Globally, there is an increase in the prevalence of anaemia in HIV-positive patients and those with AIDS, possibly due to increased blood loss from concomitant neoplasia or gastrointestinal lesions, or due to decreased red blood cell (RBC) production, RBC destruction or inefficient RBC production.…”
Section: Discussionmentioning
confidence: 99%
“…DOTA conjugates with antibodies and peptides such as hum195, j591, B4, TADOTAGA, PSMA‐617, PSMA I&T, and Crown‐αMSH are directly labeled with Ac‐225 (Abbasi et al, 2021; Maguire et al, 2014; Yang et al, 2020). X‐ray fine absorption studies have shown that the macrocyclic chelating agents like HEHA and HEHA‐NCS were also initially conjugated with targeting vector monoclonal 201B antibody and then labeled with Ac‐225 which were investigated for lungs cancer treatment (Bloch et al, 2020). Ac‐225 easily form complex with acyclic chelating agents such as EDTA and CHX‐A‐DTPA that showed very fast radiolabeling at room temperature in a very short time for in vivo therapy of liver cancer treatment (Boros & Holland, 2018; Foss et al, 2005).…”
Section: Chelation Chemistry Of Ac‐225mentioning
confidence: 99%